Glutamate alleviates intestinal injury, maintains mTOR and suppresses TLR4 and NOD signaling pathways in weanling pigs challenged with lipopolysaccharide - Qin, Qin (Sci Rep, 2018)
This experiment aimed to explore whether glutamate (Glu) had beneficial effects on intestinal injury caused by Escherichia coli LPS challenge via regulating mTOR, TLRs, as well as NODs signaling pathways. Twenty-four piglets were allotted to 4 treatments including: (1) control group; (2) LPS group; (3) LPS + 1.0% Glu group; (4) LPS + 2.0% Glu group. Supplementation with Glu increased jejunal villus height/crypt depth ratio, ileal activities of lactase, maltase and sucrase, and RNA/DNA ratio and protein abundance of claudin-1 in jejunum and ileum. In addition, the piglets fed Glu diets had higher phosphorylated mTOR (Ser(2448))/total mTOR ratio in jejunum and ileum. Moreover, Glu decreased TNF-α concentration in plasma. Supplementation with Glu also decreased mRNA abundance of jejunal TLR4, MyD88, IRAK1, TRAF6, NOD2 and increased mRNA abundance of ileal Tollip. These results indicate that Glu supplementation may be closely related to maintaining mTOR and inhibiting TLR4 and NOD signaling pathways, and concomitant improvement of intestinal integrity under an inflammatory condition.